Religious Conversion in Hadith and the Discourse of Muslim Scholars - Muttaqin, Zaenal; Sarib, Suprijati; Husain, Husain; Rahman, Rahman; Rohmah, Siti; Mokodenseho, Sabil (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This study aims to analyze the status of hadiths that serve as the basis for the imposition of sanctions on individuals who convert from Islam to other beliefs (apostasy) and the views of Muslim scholars in understanding the legal messages behind hadiths on apostasy. This study addresses questions regarding the wording, transmission, and status of hadiths on apostasy, as well as how Muslim scholars define apostasy and interpret the legal messages of apostasy sanctions in the hadiths of the Prophet. The study utilizes the method of takhrij hadith with an analytical-descriptive approach. Both primary and secondary research data are gathered from various literary sources. The study finds that hadiths on the legal sanctions for apostasy have two forms of wording: "man baddala dinahu faqtuluhu - whoever changes his religion, kill him" and "la yahilllu damumriin muslimin illa tsalasin - no Muslim's blood is lawful except for three cases." Hadiths on apostasy sanctions fall into the category of ahad hadiths with a degree of authenticity (sahih). Furthermore, the study reveals the evolution of Muslim scholars' understanding of apostasy, wherein apostasy was initially understood solely as a departure from the Islamic faith (i'tiqad) but later came to be seen as a departure accompanied by enmity towards Islam. The scholars themselves are divided into two major groups in their interpretation of the position of hadiths on apostasy, namely the classical Muslim scholars who interpret it as a legal ruling that can be implemented against apostates. In contrast, contemporary Muslim scholars have started to criticize and reinterpret the status of these hadiths, emphasizing the need to reconsider the contextualized understanding of the legal message of apostasy sanctions. The significant contribution of this study lies in clarifying the status of hadiths on apostasy sanctions and illustrating the dynamic understanding of Muslim scholars regarding the implementation of these hadiths' messages